ANALISIS PERILAKU YANG MEMENGARUHI PEMERIKSAAN ANC DI WILAYAH KERJA PUSKESMAS MAMAS KECAMATAN DARUL HASANAH KABUPATEN ACEH TENGGARA PROVINSI ACEH TAHUN 2022 - Sakinah, Ridha; Asriwati, Asriwati; Wulan, Mayang (Universitas Prima Indonesia, 2023)
Antenatal care is the care of the mother and fetus during pregnancy. Currently, the proportion of maternal deaths is approximately 305 deaths per 100 thousand live births, where the largest deaths occur in hospitals, around 77% of mothers cannot be saved, one of which is because the mothers who are referred to the hospital have severe complications. This occurs because identification and examination during pregnancy are not maximized. This study aimed to analyze behavior that influences ANC examinations in pregnant women at Working Area of Mamas Health Center, Southeast Aceh Regency, Aceh Province. This is analytical descriptive quantitative research. The population in this study were all third trimester pregnant women with late gestational age in the working area of the Mamas Health Center, Darul Hasanah District, Southeast Aceh Regency, Aceh Province in 2022 totaling 211 people. There were 68 samples in this study which were taken by Nonprobability Sampling using the slovin formula. Quantitative data analysis used univariate, bivariate and multivariate analysis. The results of the chi-square test obtained for age p= 0.000, education p=0.000, parity p=0.000, distance p=0.000, occupation p=0.000, knowledge p=0.000, husband support p=0.000 and attitude p=0.000 which indicated that there were influencing factors. The conclusion shows that there is a relationship between age, education, parity, distance, occupation, knowledge, attitude and husband's support with ANC examinations at Mamas Health Center in 2022, and the husband's support factor is the most Dominantly affect ANC examinations in pregnant women with an Exp(B) value of 4.691. It is expected that health workers at the Health Center to be more routine and intense in conveying health education to the community, especially to pregnant women and their husbands, about the importance of having ANC examination at least 6 times during pregnancy. Keywords: Age, Education, Parity, Distance, Work, Knowledge, Attitude, Husband's Support AND ANC Examination